The Chinese Adaptation of the Teachers’ Sense of Efficacy Scale in Early Childhood Pre-Service Teachers: Validity, Measurement Invariance, and Reliability - Mingxing Shao; Mohd Mokhtar Muhamad; Fazilah Razali; Nasnoor Juzaily Mohd Nasiruddin; Xinchong Sha; Guoqiang Yin (Behavioral Sciences)
Teachers’ sense of efficacy (TSE) is a crucial construct for evaluating the quality of pre-service teachers. While the Teachers’ Sense of Efficacy Scale (TSES) is the most widely used and promising instrument for measuring TSE, there is no existing literature assessing the appropriateness of the TSES for early childhood pre-service teachers in China. This study aimed to adapt the English version of the TSES for the Chinese early childhood education contexts, testing its factor structure, validity, measurement invariance, and reliability. The sample included 402 participants in China. The TSES was translated into Chinese using the standard back-to-back translation method. CFA results indicated that the TSES is best represented by a modified three-factor model, demonstrating strong preliminary, overall, and internal structure fit. The concurrent validity, convergent validity, criterion-related validity, internal consistency reliability, and composite reliability of the Chinese version of the TSES were robust. The measurement invariance across age and college year was also confirmed. This study addresses a gap in the literature by providing robust empirical evidence on the factor structure, validity, measurement invariance, and reliability of the Chinese version of the TSES for early childhood pre-service teachers, thereby enhancing understanding of TSE in Chinese-speaking Confucian culture and in early childhood education contexts.